MOBILE WALLET SYSTEM FOR STUDENTS IN BOARDING SCHOOL - ROSFAUZI, ROS DANIAL EMIR (IRC, 2020)
This paper will introduce a new implementation of existing technology that aims to help the parents to monitor their children expenditure from home. This research needs to study the existing mobile wallet system, to develop mobile wallet system for boarding school students and to evaluate the acceptance of the parents towards the usage of mobile wallet. E-wallet is an upcoming technology that has been a tremendous growth in the past year. Nowadays, most of boarding school has allowed the students to bring their smartphone with certain regulations that need to obey. The parents able to track the history transaction and observe the pattern amount of money spent by their kids by using smartphone. To conduct the preliminary studies, literature review of the project and surveying to the potential users will be done. For the mobile application development, Rapid Application Development (RAD) model will be apply for the System Development Life Cycle (SDLC) technique. E-wallet has a great potential to help the students in their spending without bringing cash money while their parents can observe their children expenditures.